Materiality And Risk Essential Pillars Of The Auditor’s Work - Maqellari, Majlinda; Dika, Ines (European Scientific Journal, ESJ, 2016)
This paper reports interview evidence on audit materiality and the answers to the variables regarding how the materiality of gray area (± 5% of defined materiality) determines the auditors’ opinion. Focus-Groups Questionnaires is a Method of Collecting Qualitative Data, in our case, 215 Certified Public Accountants (CPA) from Authorized Accountant Experts Institute (IEKA), Albania. Opinion of the auditors about the financial statements, in cases of gray materiality´s area depends on the experience or the substantive audit procedures. We have designed questionnaires regarding audit judgment based on the experience, gender, risk assessment, age. We have scrutinized albanian CPA giving a priority calculations and tests versus experience. The Albanian auditor characteristic in professional judgment, is dependeble on substantive procedures, but auditors use their experience on enterprises operating in the same feld. The young experts use professional judgment more than personal judgment.